2020
DOI: 10.1055/a-1119-6673
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of 25-gauge Franseen needles for endoscopic ultrasound-guided fine-needle biopsy of solid pancreatic masses

Abstract: Background and study aims The ideal puncture needle for endoscopic ultrasound (EUS)-guided sampling is maneuverable and easy to puncture with, and can obtain sufficient material in almost one pass. The novel 25-gauge Franseen needle may provide a good balance between maneuverability and sample yield. Patients and methods Between July 2017 and December 2018, 116 patients with solid pancreatic masses were prospectively enrolled and investigated. We evaluated the diagnostic yield associated with using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Therefore, if the diagnostic yields among different‐sized needles are equal, a thinner needle would be preferable. Two previous studies reported the outcome of EUS‐FNB with the 25G Franseen needle, reporting adequate tissue acquisition rates of 79.3% and 95.0%, respectively 17,18 . In this study, the 25G Franseen needle was comparable to the 22G needle in terms of procurement of adequate tissue samples from pancreatic masses.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Therefore, if the diagnostic yields among different‐sized needles are equal, a thinner needle would be preferable. Two previous studies reported the outcome of EUS‐FNB with the 25G Franseen needle, reporting adequate tissue acquisition rates of 79.3% and 95.0%, respectively 17,18 . In this study, the 25G Franseen needle was comparable to the 22G needle in terms of procurement of adequate tissue samples from pancreatic masses.…”
Section: Discussionsupporting
confidence: 49%
“…Two previous studies reported the outcome of EUS-FNB with the 25G Franseen needle, reporting adequate tissue acquisition rates of 79.3% and 95.0%, respectively. 17,18 In this study, the 25G Franseen needle was comparable to the 22G needle in terms of procurement of adequate tissue samples from pancreatic masses. Moreover, sampling with the 25G needle provided equivalent diagnostic accuracy to the 22G needle, although EUS-FNB was technically easier with 25G than with 22G.…”
Section: Discussionmentioning
confidence: 78%
“…The differences between the 22- and 25-gauge FNB needles have not been extensively studied. Two studies detailed the performance of 25-gauge FNB Franseen needles, reporting sample adequacy rates of 79 and 82%, respectively, which may be inferior to the aforementioned rates for 22-gauge needles [ 22 , 23 ]. A randomized prospective study compared diagnostic yields for 25- and 22-gauge Franseen needles in patients with solid pancreatic lesions finding no significant difference in diagnostic yield (98 vs. 88%, p = 0.105, respectively), however finding that the 25-gauge group required additional passes to obtain an adequate cell block (1.6 ± 0.6 vs. 0.4 ± 0.7, p = 0.001) [ 24 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In a recent meta-analysis of seven randomized controlled trials (RCTs), 44 a 25-gauge FNA needle is not superior to a 22-gauge FNA needle in sensitivity and adequacy for the diagnosis of SPLs. As described above, estimated pooled ORs in our meta-analysis suggested the lower sensitivity in small SPLs was less prominent when a 25-gauge needle was used (Figure 5a), as compared to studies without the use of a 25gauge needle.However,there has been no head-to-head comparative study of 25-and 22-gauge needles in small SPLs.Furthermore,effectiveness of 25-gauge FNB needles has been reported in SPLs, [45][46][47] though one study did suggest sensitivity and adequacy decreased in small SPLs even using a 25-gauge FNB needle. 47 A prospective comparative study is warranted to elucidate whether a 25-gaguge FNA or FNB needle would provide better diagnostic yield in small SPLs or not.…”
Section: The Needle Sizementioning
confidence: 99%
“…However, there has been no head‐to‐head comparative study of 25‐ and 22‐gauge needles in small SPLs. Furthermore, effectiveness of 25‐gauge FNB needles has been reported in SPLs, 45 , 46 , 47 though one study did suggest sensitivity and adequacy decreased in small SPLs even using a 25‐gauge FNB needle. 47 A prospective comparative study is warranted to elucidate whether a 25‐gaguge FNA or FNB needle would provide better diagnostic yield in small SPLs or not.…”
Section: Introductionmentioning
confidence: 99%